The Economic Consequences of Debilitating Illness: The Case of Multiple Sclerosis - Inman, Robert P. (The Review of Economics and Statistics, 1987)
The economic consequences of debilitating illness are defined and then estimated for one such illness–multiple sclerosis. Economic losses are defined as the consumption losses to the affected household because of illness. These losses are measured as the change in earnings of all family members plus the increase in gross (not out-of-pocket) medical costs. Earnings models are specified and estimated, and gross medical costs calculated for multiple sclerosis. The average annual loss to the multiple sclerosis household is $5, 336 per year in 1976 dollars; the estimated aggregate decline in consumption for the year 1976 was $0.656 billion. Lifetime costs (discounting by 0.06) total $207, 200 per multiple sclerosis household and $25.50 billion for society as a whole for the current (1976) pool of multiple sclerosis patients, and $30.45 billion for all future multiple sclerosis patients. Copyright 1987 by MIT Press.